Organic-inorganic dipolar and quadrupolar coupling underlies the structure and properties of hybrid perovskites - Mozur, Eve M., author; Neilson, James R., advisor; Prieto, Amy, committee member; Krummel, Amber, committee member; Sites, James, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.
Keywords: neutron scattering; solid state chemistry; dynamics; structure; perovskite